A hybrid evolutionary algorithm: multirecombination with priority rule base representation abstract for the job shop scheduling problem - Salto, Carolina (2000)
A variety of optimization problems in fields such as production operations in manufacturing industry, parallel and distributed systems, logistics and traffic can be summarized within the general class of scheduling problems. A common feature of this problems is that they belong to the class of NP-complete problems, which means that no deterministic algorithm is known yet for solving them in polynomial time. The major advantage of evolutionary techniques resides in their ability of providing good solutions to extremely complex problems in reasonable time. This work introduces MCMP-PRB to face the Job Shop Scheduling Problem (JSSP). Enhancements include a multiplicity feature (MCMP) and a further hybridization with a conventional heuristic know as the priority dispatching rule.